ZACHARIAH SCHOLASTICUS AND THE HISTORIA ECCLESIASTICA OF EVAGRIUS SCHOLASTICUS - Allen, Pauline (The journal of theological studies, 1980)
PAULINE ALLEN; ZACHARIAH SCHOLASTICUS AND THE HISTORIA ECCLESIASTICA OF EVAGRIUS SCHOLASTICUS, The Journal of Theological Studies, Volume XXXI, Issue 2, 1 Octob